The Interview Times : YAEL | Buraxılış No.9 | Mart, 2023 - El Presidente; Kamanga, Nathan; Duran, Alejandra Garcia (ADA University, 2023)
YAEL, her Azerbaijani name is Nargiz Musayeva and is originally from Azerbaijani mountain Jews. She is a graduate of ADA University and currently works as a manager at the Jewish organization "Enerjew" located in Minsk. At the same time, she conducts individual English lessons and organizes conversations. She lives in Baku and is married to Martin, a German she met in the United States.

In order to read full interview, click View/Open section below.
Keywords: ADA University--Newspaper.